Comparação da infiltração marginal de restaurações adesivas empregando instrumento rotativo ou um sistema químico-mecânico na remoção do tecido cariado - Naressi, Suely Carvalho Mutti [UNESP] (1999)
The chemo-mechanical removal of carious tissue using Carisolv (MediTeam) presents several advantages and indications, when lasting adhesive fillings are expected. This research proposes to compare the sealing conditions of adhesive restorations placed on teeth submitted either to the chemo-mechanical method using Carisolv or to the traditional bur method of caries removal. Sixty decayed human molars received, after the removal of the carious tissue, adhesive fillings of Vitremer (3M), Dyract (Dentsply DeTrey) e TPH Spectrum (Dentsply DeTrey). The microleakage was observed using the 0,2% Rodamine B dye method in all the samples. The samples were sectioned and examined under optical stereomicroscopy. The statistical analysis using the Kruskall-Wallis and Mann-Whitney non-parametrics tests showed the existence of marginal leakage in most samples; the differences observed in the materials tested were not significant when the traditional method was used but a statistically significant difference existed when Carisolv was employed; the highest levels of microinfiltration occured with Vitremer and the sealing properties of the various adhesive materials were not influenced by the caries removal method applied